The Role of ESG in Enhancing Stock Robustness Through Economic Downturns : An empirical analysis of the European Market (Stoxx Europe 600) - Nguyen, Thi Hao (2025)
The dissertation studies the role of ESG in enhancing corporate resilience during crises, specifically the Global Financial Crisis in 2008 and the COVID-19 pandemic in 2020. The study was conducted on 283 publicly traded companies from the STOXX Europe 600 index to find evidence that companies with higher ESG ratings perform better in their finances during a market crisis. The study uses a cross-sectional regression model on ESG Scores, and the respective pillars of Environmental, Social, and Governance, and firm performance to analyze how ESG ratings are linked to important performance metrics as Tobin’s Q, stock returns, Return on Assets (ROA), Return on Equity (ROE), and Sharpe ratios. The conclusion says that companies that perform better on ESG were better at keeping their financial stability and investor trust. Governance and social factors were more closely linked to performance resilience. The results substantiate ESG integration as both a long-term sustainability strategy and a short-term risk mitigation instrument during systemic risk. The study’s findings demonstrate that ESG performance does, in fact, have a significant effect on firm performance and support the stakeholder theory viewpoint over the principal-agent theory. Future studies could examine whether the findings of this study can be repeated in other eras and geographical locations, or whether other events have significantly contributed to the growing significance of ESG.